BBC Drama and the Politics of Production 1955-66 - Joy Leman (Revue Française de Civilisation Britannique)
This paper offers a critical perspective regarding the British Broadcasting Corporation, briefly touching on the early years, the dominance of radio, and the struggle to obtain recognition and resources for television production. The management structures, policies and decision making of the BBC will be considered, with reference to consequences for practitioners and for the form and content of programmes broadcast.